The Melanocortin MC5R as a New Target for Treatment of High Glucose-Induced Hypertrophy of the Cardiac H9c2 Cells - Trotta, Maria Consiglia; Maisto, Rosa; Alessio, Nicola; Hermenean, Anca; D’Amico, Michele; Di Filippo, Clara (Frontiers in Physiology, 2018)
Abstract The study explored the anti-hypertrophic effect of the melanocortin MC5R stimulation in H9c2 cardiac myocytes exposed to high glucose. This has been done by using α-MSH and selective MC5R agonists and assessing the expression of GLUT4 and GLUT1 transporters, miR-133 and urotensin receptor levels as a marker of cardiac hypertrophy. The study shows for the first time an up-regulation of MC5R expression levels in H9c2 cardiomyocytes exposed to high glucose medium (33mM D-glucose) for 48 hours, compared to cells grown in normal glucose medium (5.5mM D-glucose). Moreover, H9c2 cells exposed to high glucose showed a significant reduction in cell viability (-40%), a significant increase in total protein per cell number (+109%), and an increase of the urotensin receptor expression levels as an evidence of cells hypertrophy. The pharmacological stimulation of MC5R with α-MSH (90 pM)of the high glucose exposed H9c2 cells increased the cell survival (+50,8%) and reduced the total protein per cell number (-28,2%) with respect to high glucose alone, confirming a reduction of the hypertrophic state as per cell area measurement. Similarly, PG-901 (selective agonist, 10−10 M) significantly increased cell viability (+61,0 %) and reduced total protein per cell number (-40,2%), compared to cells exposed to high glucose alone. Interestingly, the MC5R agonist reduced the GLUT1/GLUT4 glucose transporters ratio on the cell membranes exhibited by the hypertrophic H9c2 cells and increased the intracellular PI3K activity, mediated by a decrease of the levels of the miRNA miR-133a. The beneficial effects of MC5R agonism on the cardiac hypertrophy caused by high glucose was also observed also by echocardiographic evaluations of rats made diabetics with streptozotocin (65 mg/kg i.p.). Therefore, the melanocortin MC5R could be a new target for the treatment of high glucose-induced hypertrophy of the cardiac H9c2 cells.